Mastery of pre-reading skills (vowels) of a preschool student using the VOKAD method - Bordin, Siti Norzehan; Said, Rozita Radhiah; Md Sabil, Azhar; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2022)
Reading skills are highly emphasized in the MOE Preschool Curriculum and Assessment Standard Document as they are crucial in developing students' oral communication and basic literacy throughout their schooling years. However, some preschool students struggle in mastering pre-reading skills (vowel letters) even after the first three months of instruction. As a result, they are also likely to lag behind their peers in mastering reading. Thus, an action research using the VoKad method was conducted to help improve the mastery of pre-reading skills (vowel letters) among preschool students who are struggling in reading as well as to help teachers in supporting students with these challenges. The researcher utilized the “edutainment” approach in this study which combines reading and singing techniques using the VoKad method. All instruction was carried out in the Malay language. Three teaching and learning activities were conducted over a period of one month. The findings of the study showed a very encouraging improvement in the first two weeks of intervention and the students successfully mastered all the vowel letters and sounds after four weeks of the study implementation. It is important to note that pre-reading skills do not only concern the mastery of vowels but also the skills of recognising and pronouncing consonants and segmenting open syllables. Therefore, the researchers suggest that future studies should also investigate and address students difficulty in mastering other pre-reading skills such as recognising and pronouncing consonants.